The Effectiveness of Offline and Online Campaigns towards Eco-Friendly Attitude and Intention in Reducing The Use of Plastic Cups - Inggrid, Inggrid; Boer, Rino Febriano (APMBA (Asia Pacific Management and Business Application), 2024)
This study examines the impact of both offline and online campaigns partially and simultaneously on eco-friendly intentions with the mediating role of eco-friendly attitudes in the beverage industry, specifically on bubble tea brands. This study was conducted using a quantitative approach by distributing questionnaires to offline and online customers, sampling 400 respondents, and utilizing SmartPLS 3 for hypothesis testing. The results show that the indirect impact of online campaigns has a greater influence on eco-friendly intentions through eco-friendly attitudes, whereas the direct impact of offline campaigns has a greater influence on eco-friendly intentions. Additionally, online campaigns have a greater effect on eco-friendly attitudes compared to offline campaigns. The online campaign plays a significant role in building positive perceptions before individuals act in the field. Seeing the high response from customers that the online campaign made them aware of plastic waste, it is recommended that other bubble tea brands who want to create a similar campaign create content on Instagram that highlights the negative impact of plastic on the environment.